2008
DOI: 10.1111/j.1540-6210.2008.01938.x
|View full text |Cite
|
Sign up to set email alerts
|

Being There Matters—Redefining the Model Public Servant: Viola O. Baskerville in Profile

Abstract: Civic trailblazing comes more easily to some than to others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The leadership qualities that some scholarship suggests are disproportionally exercised by and associated with women are also those demanded of successful network managers. Public administrators who exhibit a more collaborative and participatory management style and the skills required of it tend to work more effectively in horizontal power-sharing structures (Hutchinson & Condit, 2009;Koliba et al, 2010;Lewis, 2006), a management style that has been historically labeled as feminine because of its connection to the work of the settlement women (Hutchinson & Condit, 2009;Stivers 2000Stivers , 2002Wajcman, 1996). It is a label that also directly challenges antiquated gender conceptualizations that continue to influence the essential qualities people feel public managers should embody.…”
Section: The Role Of Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…The leadership qualities that some scholarship suggests are disproportionally exercised by and associated with women are also those demanded of successful network managers. Public administrators who exhibit a more collaborative and participatory management style and the skills required of it tend to work more effectively in horizontal power-sharing structures (Hutchinson & Condit, 2009;Koliba et al, 2010;Lewis, 2006), a management style that has been historically labeled as feminine because of its connection to the work of the settlement women (Hutchinson & Condit, 2009;Stivers 2000Stivers , 2002Wajcman, 1996). It is a label that also directly challenges antiquated gender conceptualizations that continue to influence the essential qualities people feel public managers should embody.…”
Section: The Role Of Gendermentioning
confidence: 99%
“…Fox and Schuhmann (1999) found that women prefer working within “webs of interaction” more than in top-down structures. Other scholars have established that women naturally tend to apply a more integrative, collaborative, cooperative management style (Fine, 2007; Hutchinson & Condit, 2009; Mani, 2009; Rosenthal, 1998; Wajcman, 1996), which is likely a result of their desire to create work environments characterized by mutual respect among employees, census decision-making, and a lack of competition for power (Flammang, 1985; Hutchinson & Condit, 2009). Studies specifically focused on women in top management positions reveal similar findings, concluding that women leaders are more persuasive, more empathetic, more flexible, and possess stronger interpersonal skills than their men counterparts (Caliper Corporation, 2005; Mani, 2009).…”
Section: The Precedent Of the Settlement Womenmentioning
confidence: 99%